Evaluasi Penentuan Daerah Kawasan Ekonomi Khusus (KEK) di Wilayah Jawa Tengah - Abdul Aziz Ahmad; Endang Setiasih (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2009)
This research evaluates determination of Special Economic Region or Kawasan Ekonomi Khusus (KEK) in Central Java – Yogyakarta Province. On regional typology aspect, counted by economic growth and per capita income, determination of KEK by Central Java Governor tends not to base by the factors. It is proofed by Demak, Rembang, and Blora Regency which enacted to be special economic region even these regencies left behind other regions relatively. Nevertheless, Kendal Regency that planned to be basis of Central Java KEK has superiority and potential in industrial sectors. But in regional typology, this area is classified by advanced but suppressed region; high per capita income but low economic growth. Alternatively, Joglosemar triangle area has interesting note. The three towns: Yogyakarta, Surakarta and Semarang Town, shows advance and grow faster typology. These areas also have better infrastructure than other regencies/towns. The development in Joglosemar corridor will have positive agglomeration effect to contiguous areas. Keywords: KEK, regional typology, agglomeration